2019
DOI: 10.1093/gastro/goz014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of subtotal colectomy with antiperistaltic caecorectal anastomosis vs total colectomy with ileorectal anastomosis for intractable slow-transit constipation

Abstract: BackgroundFew studies have compared the surgical outcomes of different surgical procedures currently used to treat refractory colonic slow-transit constipation (STC), despite the increase in the number of cases. This study aimed to analyse the long-term surgical outcomes of subtotal colectomy with antiperistaltic caecorectal anastomosis (SC-ACRA) vs total colectomy with ileorectal anastomosis (TC-IRA) for severe STC.MethodsBetween January 2005 and January 2015, we retrospectively collected clinical data of 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…may improve FC symptoms by promoting colon secretion and enhancing gastrointestinal motility [ 9 ]. Other treatment options with evidence for efficacy include biofeedback therapy [ 13 ], transanal irrigation [ 14 ], surgical interventions [ 15 , 16 ], and neuromodulation [ 14 ]. Despite all these intervention options, 40% of pediatric [ 17 ] and more than half of adult FC patients [ 18–20 ] are dissatisfied with the treatments due to the lack of efficacy and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…may improve FC symptoms by promoting colon secretion and enhancing gastrointestinal motility [ 9 ]. Other treatment options with evidence for efficacy include biofeedback therapy [ 13 ], transanal irrigation [ 14 ], surgical interventions [ 15 , 16 ], and neuromodulation [ 14 ]. Despite all these intervention options, 40% of pediatric [ 17 ] and more than half of adult FC patients [ 18–20 ] are dissatisfied with the treatments due to the lack of efficacy and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…If they are, surgery should be cautiously entertained but not abandoned [13]. Recent retrospective surgical series have consistently identified preoperative abdominal pain and bloating, via SF-36 questionnaires, Wexner Constipation Scores, or Gastrointestinal Quality of Life scores to be present in preoperative patients [69][70][71]. In each of these series, symptoms were significantly improved postsurgery.…”
Section: Abdominal Colectomymentioning
confidence: 99%
“…Despite reporting satisfactory results, there are few comparative studies looking at these technical variations. Xie et al compared 20 patients who had abdominal colectomy with antiperistaltic cecorectal anastomosis to 35 who had standard ileorectal anastomosis and found no difference in postoperative outcomes including Wexner Constipation scores, Cleveland Clinic Incontinence and Constipation scores, as well as Gastrointestinal Quality of Life scores [71].…”
Section: Abdominal Colectomymentioning
confidence: 99%
“…However, the best surgical procedure for STC has been debated for decades: the complexity of patients and disease, along with the difficulty of expressing or quantifying symptoms, makes a comparative study hard to perform. A recent series by Xie et al found no differences between antiperistaltic caecorectal anastomosis (SCCRA) and total colectomy with ileorectal anastomosis in terms of postoperative quality of life and incidence of complications [3]. Nevertheless, Patton et al [1] reported a significant deterioration in continence after total colectomy with ileorectal anastomosis on long‐term follow‐up.…”
Section: Figurementioning
confidence: 99%